Public Action in the Fight against HIV/Aids Actors, Controversies and Dynamics. A Comparative Analysis of South African, Burkinabe and Cameroonian Cases - (:unkn) unknown (My University, 2009)
For more than twenty-five years, human and social sciences have been trying to understand and to interpret the dynamics of the HIV/AIDS epidemic. However, African studies in political science are at the margins of this cognitive movement despite the development of paradigms on public policies. This mistrust of Africanist towards HIV/AIDS research expresses an epistemological limitation related to the dominance of institutional and statist approaches that still characterize African studies in political science. An outcome of this mistrust is a disinterest in non-state social actors that are active in the making of political objects, especially considering the absence of the state in the governance of HIV/AIDS in Africa. However, the HIV/AIDS epidemic incontestably produces political effects: it generates and maintains power struggles; it questions the mechanism of the governance of social problems; it reveals the withdrawal of the state from public space in favour of non-elected but participative forms of entry into public space. As a result the HIV/AIDS epidemic necessitates the renewal of research paradigms on the state in Africa and their transposition onto the civil actors that emerge alongside the state in the fight against HIV/AIDS. This thesis analyses the dynamics of the HIV/AIDS epidemic using political science theories and concepts and a comparative approach to the role and the place of political and associative actors, the controversies and the epidemic dynamics, in the political construction of HIV/AIDS in South Africa, Burkina Faso and Cameroon.
Keywords: African Research